Speeches given by Alexander George William Keys - Keys, William (Alexander George William), Sir, 1923-2000.; Returned Services League of Australia (1970)
1. Speech given by William Keys to members of Rotary at Woden Valley R.S.L. Club on the 5th August 1970; 2. Address at Nowra 18.3.77; 3. Address to Queensland Southeast District Conference, Sandgate, 19.2.77 (photocopies); 4. "Korea revisited" and "The R.S.L." an address to RAAF Staff College, 27.8.76.
Manuscript reference no. : MS 2876.
Mr A.G.W. Keys, O.B.S. was the National Secretary of the Returned Soldiers League.
Keywords: Keys, William -- Sir, -- 1923-2000.